Book Review - Sonny Shiu-Hing Lo. The New Politics of Beijing-Hong Kong Relations: Ideological Conflicts and Factionalism - Xie, Colin Mianqing (INTERNATIONAL JOURNAL OF CHINA STUDIES, 2025)
In this cutting-edge and exceptional book on Beijing-Hong Kong relations, Sonny Lo provides a comprehensive and up-to-date analysis of Beijing-Hong Kong relations, particularly in the post-national security law era. Moreover, this book understands the alterations in Hong Kong’s political landscape over the last two decades from both perspectives of Beijing and the Hong Kong Special Administrative Region (HKSAR) governments, as well as Hong Kong democrats and localists.